Evaluation of Cervical Microleakage of Different Restorative Materials in Class V Restorations: in vitro Study - Zanbaq Azeez Hanoon; Amal Qasim Ahmed; Sattar Jabbar Abdul-Zahra Al-Hmedat; Salah M.Ibrahim (International Journal of Medical Toxicology and Legal Medicine, 2024)
Aim: The purpose of this study was to evaluate the cervical microleakage ofMicro-hybrid (Charisma Classic), Nano-hybrid (EsCom 100)and Nano-ceramic (ZENIT) resin composites for class V restorations. Materials and Methods: Forty-five human upper 1st premolars were randomly divided into three study groups (n = 15). Standardized class V cavity preparation was carried out on the buccal surface of each tooth sample. After cavity preparation, acid etching of the cavities was performed with 37% phosphoric acid etchant gel. Single Bond Universal Adhesive was applied to the etched enamel and dentin. A dental composite instrument was used for composite filling. After finishing and polishing the class V composite restorations, the samples were kept in distilled water for 2 weeks at 37°C. All the specimens were subjected to a thermocycling procedure (500 cycles at 5-55°C) and then immersed in 2% methylene blue dye for two days. All specimens were blocked with clear acrylic before sectioning. The means of cervical microleakage were recorded using a digital microscope and the ImageJ software. Results: The lowest mean amount of microleakage was recorded for Group C (66.4380 ± 4.66391), which was restored with the ZENIT composite, while the highest mean amount of microleakage was recorded for Group A (92.7673±3.40694), which was restored with the Charisma classic composite. The Tukey HSD results showed that the type of composite filling material had a highly significant effect on marginal microleakage (P ≤ 0.01). Conclusions: Althoughnone of the tested restorative materials completely sealed the cervical margin,theZENIT nanoceramic composite showed significantly less marginal microleakage than the EsCom 100 nanohybrid and Charisma classic microhybrid composites. Clinical significance:The potential to improve patient outcomes by providing data that supports the selection of composite resins like ZENIT to minimize microleakage and enhance the long-term success and aesthetics of Class V restorations. This contributes to more predictable and durable restorative dentistry.